Mapping religion and spirituality in a postsecular world - Giordan, Giuseppe; Pace, Enzo. (Leiden ; Boston : Brill, 2012)
This volume offers eleven case studies of contemporary movements from around the world where religious, secular and spiritual dynamics interplay in the postmodern condition of the 21st century, as traditional and contemporary sources are combined in new and dynamic ways.
Description based upon print version of record.
Keywords: Religion -- Philosophy; Religion -- History -- 21st century; Spirituality -- History -- 21st century; Religion -- History -- 21st century; Religion -- Philosophy; Spirituality -- History -- 21st century; Religion; RELIGION / History; TRAVEL / Special Interest / Religious; Electronic books